SURVEI TINGKAT KEMAMPUAN VO2 MAX WASIT BOLABASKET INDONESIAN BASKETBALL LEAGUE - Rahmat Iqbal; Johanes Paulus Suharto; Arnaz Anggoro Saputro (STKIP PGRI Jombang, 2021)
In being a basketball referee, he is required to be in good shape while in charge of leading the match, so in this case the researcher wants to know the VO2 Max ability of the Indonesian Basketball League basketball referee for the 2020-2021 season. The purpose of this study was to determine the ability of VO2 Max basketball referees in Indonesian Basketball League basketball referees for the 2020-2021 season. This study used a descriptive method with a test survey method. The study population was all basketball referees for the Indonesian Basketball League 2020-2021 season totaling 24 referees. Sampling in this study using total sampling technique. Of the 24 samples above VO2 Max is very good, good, sufficient, and moderate. The test and measurement technique is done by using multistage running (multistage fitness test) to measure VO2 Max. Based on the research results, the following conclusions were obtained; The physical ability of basketball referees in the Indonesian Basketball League, out of the 24 referees that we categorized as good, there were 3 with a percentage of 12.5% in the fair category, 17 referees with a percentage of 70.83% and 4 referees in the poor category with 16.6% and average value In conclusion, the researchers can say that physical training is still needed to add VO2 Max referees who are referees for Indonesian Basketball League basketball while leading the match in prime condition.